CLIL model of teaching in the College English curriculum in China: policies, perceptions, and practices - Li , Shujing (Onomázein, 2021)
Adopting a CLIL perspective, this study investigates the policies, perceptions, and practices concerning the courses that claim to integrate content learning and language learning in the Chinese College English context by using both a quantitative research method and a qualitative research method. The quantitative study focuses on both learners’ and teachers’ motivation intensity, motivation types, gains in participating in the CLIL courses, and their general attitudes toward the courses. A questionnaire is conducted with 2513 College English students and 230 College English teachers from 45 universities that fall into three different levels and three major types. The qualitative study examines the current state of the CLIL-type College English curricula mainly through the analyses of the College English syllabi provided by 24 universities of different levels and other documents, and also explores the notions of the policy-makers at the university level in regard to CLIL courses through an interview with 15 College English teacher-administrators.